INOVASI USAHA KERIPIK TALAS SITUJUH MELALUI PACKAGING DAN PEMANFAATAN BAWANG PUTIH SEBAGAI ANTIOKSIDAN - Tri Rahayuningsih; Rani Armalita; Annisa Fauzana; Maulidya Maulidya; Elisa Fepri Nengsih (LPPM Universitas Andalas, 2021)
The number of consumer demands for Mitra's taro chips has not been fulfilled due to limited production, which is still traditional using manual equipment and because of the lack of knowledge about business planning and the lack of business development strategies through the application of the marketing mix (4P) using information technology and computers in response to the Covid-19 pandemic. 19. Therefore, Partners need process innovation in the form of modern equipment for product packaging. Paradigm changes to be able to adapt in maintaining their business by using garlic as an antioxidant as a natural preservative for taro chips, as well as knowledge of marketing applications using internet technology to meet consumer demand and reach a broader market. Besides that, it also pays attention to aspects of business legality, such as having a business license to ensure product quality and maintain customer trust. This activity aims to help partners develop their business in the snack food sector, namely taro chips that continue to grow in Tungkar Village, Situjuah District, Limo Nagari through equipment assistance and 4P marketing mix strategies these micro-businesses can survive and increase their results. Partners' theoretical benefits from this activity will be to gain knowledge about business strengthening through innovation (paradigms and processes). Practically, Partners will get business development assistance through more modern equipment for packaging taro chips that are durable and long-lasting. Partners can implement marketing strategies from the 4P aspect using internet technology to reach consumers more broadly.